2018
DOI: 10.1002/pat.4400
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect between a novel triazine‐based flame retardant and DOPO/HPCP on epoxy resin

Abstract: In this paper, a triazine‐based flame retardant (TAT) was synthesized from cyanuric chloride and aniline. Its chemical structure was characterized by Fourier transform infrared (FTIR) spectroscopy, 1H nuclear magnetic resonance, and elemental analysis. Two kinds of novel intumescent flame‐retardant epoxy systems were obtained with the incorporation of TAT and 9,10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO) or hexa‐phenoxy‐cyclotriphosphazene (HPCP). The flame retardancy of the obtained epoxy samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…A lower pk‐HRR value means better fire resistance 26 . On the other hand, the THR value of a material reflects its combustion intensity, and the higher the THR is, the greater the combustion intensity will be 27 . The changes in the values of these two indicators for the different samples are discussed below.…”
Section: Resultsmentioning
confidence: 99%
“…A lower pk‐HRR value means better fire resistance 26 . On the other hand, the THR value of a material reflects its combustion intensity, and the higher the THR is, the greater the combustion intensity will be 27 . The changes in the values of these two indicators for the different samples are discussed below.…”
Section: Resultsmentioning
confidence: 99%
“…It is noted that both PLA‐4 and PLA‐7 exhibit a long stable burning stage. That is speculated to the decomposition of flame retardants can release PO• radical to react with active radicals from oxygen and thus suppress flame development . In Figure B, all the PLA composites have smaller THR values in comparison with PLA‐0.…”
Section: Resultsmentioning
confidence: 92%
“…During recent years, phosphorus‐containing flame retardants such as 9,10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO) and its derivatives; red phosphorus (RP); hexa‐phenoxy‐cyclotriphosphazene (HPCTP) and its derivatives; ammonium polyphosphate (APP); and aluminum diethylphosphinate (OP) have been used as halogen‐free flame retardants for EP modification. Many works were carried out using DOPO, HPCTP, and their derivatives as flame retardants for EP, due to good flame retardancy and acceptable impacts on the various properties of EP . Zhang and coauthors reported four‐functional flame retardants prepared from HPCTP or DOPO.…”
Section: Introductionmentioning
confidence: 99%
“…Many works were carried out using DOPO, HPCTP, and their derivatives as flame retardants for EP, due to good flame retardancy and acceptable impacts on the various properties of EP . Zhang and coauthors reported four‐functional flame retardants prepared from HPCTP or DOPO. Limited oxygen index (LOI) and vertical burning tests (UL‐94) showed that EP/HPCTP thermosets possessed better flame retardant properties than EP/DOPO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation